Short Notes on the Vertebrate Fauna of Ayer Hitam Forest Reserve, Puchong, Selangor - Ali Haji, Jambaari; S., Rajagopal; Yaacob, Azmi (Universiti Putra Malaysia Press, 1999)
Record from the Museum of Zoology, Department of Biology, Universiti Putra Malaysia contains list of vertebrates of Ayer Hitam Forest Researve area collected from 1975 until 1985. The collection in the museum consists of 14 birds, 10 anurans, 5 lacertalians, 3 ophidians and 8 mammals. Recent field collections by students of biology, as part of their assignment of vertebrates diversity revealed 3 species of bats, 2 reptiles, 13 anurans and 10 fishes. Fish is the new addition of the vertebrate lists that was not collected before. The list of vertebrate in this report is lJy no means exhaustive. More collections are needed to inventories the vertebrates of Ayer Hitam Forest Reserve.